MMSE filter design for Full-Duplex filter-and-forward MIMO relays under limited dynamic range - Emilio Antonio-Rodríguez; Stefan Werner; R. López-Valcarce; Risto Wichman (Signal Processing, 2019)
We study the problem of optimizing the end-to-end performance of a full-duplex filter-and-forward MIMO relay link, consisting of a source, a relay, and a destination node, by employing linear filtering at each node. The system model accounts for multipath propagation and self-interference at the relay, as well as transmitter impairments and limited dynamic range at every node. The design accommodates signals with arbitrary spectra and includes the direct link between the source and destination nodes. Under the minimum mean square error criterion, the resulting non-convex problem is approximated by a sequence of convex problems and solved by means of an alternating minimization method. Linear constraints allocate some of the degrees of freedom in the relay to guarantee a sufficiently small residual self-interference. Simulations quantify the impact of degrees of freedom, the dynamic range, and the balance between direct and relay paths on the link performance.
Keywords: adaptive signal processing; full-duplex; winter

Wideband full-duplex MIMO relays with blind adaptive self-interference cancellation - Emilio Antonio-Rodríguez; Stefan Werner; R. López-Valcarce; Taneli Riihonen; Risto Wichman (Signal Processing, 2017)
We develop adaptive self-interference cancellation algorithms for both filter-and-forward and decode-and-forward multiple-input multiple-output relays. The algorithms are blind in the sense that they only exploit the spectral properties of the transmitted signal to identify the self-interference channel, while dealing with frequency-selective channels and arbitrary signal spectra. Our approach is non-intrusive in the sense that the algorithms can successfully identify, track, and cancel the self-interference distortion while the relay is operating in its normal mode. We study the stationary points of the algorithms and analyze under which conditions they achieve perfect cancellation of the self-interference. Simulation results show that the algorithms provide residual self-interference levels below the noise floor by using the time samples of only a few OFDM symbols.
Keywords: adaptive signal processing; compass; full duplex; winter

Subspace-constrained SINR optimization in MIMO full-duplex relays under limited dynamic range - Emilio Antonio-Rodríguez; R. López-Valcarce; Taneli Riihonen; Stefan Werner; Risto Wichman (IEEE 16th Int. Workshop on Signal Processing Advances in Wireless Communications (SPAWC), 2015)
We propose a method for maximizing the signal-to-interference-plus-noise ratio (SINR) in a wideband full-duplex MIMO regenerative relay that accounts limited dynamic range of the receiver and transmitter impairments. Transmit and receive filters are designed at the relay, by means of an alternating minimization algorithm, to minimize the interference at the decoder input in the destination node. We impose channel shortening and subspace constraints to ensure that the received signal at the destination is not compromised. Simulation results show that the presented method significantly outperforms other constrained approaches.
Keywords: adaptive signal processing; compass; full duplex

SINR Optimization in Wideband Full-Duplex MIMO Relays under Limited Dynamic Range - Emilio Antonio-Rodríguez; R. López-Valcarce; Taneli Riihonen; Stefan Werner; Risto Wichman (IEEE Sensor Array and Multichannel Signal Processing Workshop (SAM), 2014)
Keywords: adaptive signal processing; compass; full duplex

Adaptive Self-interference Cancellation in Wideband Full-Duplex Decode-and-Forward MIMO Relays - Emilio Antonio-Rodríguez; R. López-Valcarce; Taneli Riihonen; Stefan Werner; Risto Wichman (IEEE 14th Int. Workshop on Signal Processing Advances in Wireless Communications (SPAWC), 2013)
Keywords: adaptive signal processing; dynacs; full duplex

Autocorrelation-based adaptation rule for feedback equalization in Wideband Full-Duplex Amplify-and-Forward MIMO relays - Emilio Antonio-Rodríguez; R. López-Valcarce; Taneli Riihonen; Stefan Werner; Risto Wichman (Int. Conf. Acoust., Speech, Signal Process. (ICASSP), 2013)
Simultaneous reception and transmission in the same frequency, so-called full-duplex operation, causes an infinite feedback loop in an amplify-and-forward relay. The unwanted echoes may result in oscillation at the relay, making it unstable, and distorting the spectrum. This paper presents an adaptive MIMO filtering method for full-duplex amplify-and-forward relays that aims at solving the joint problem of self-interference mitigation and equalization of the source-relay channel. The scheme exploits knowledge of the autocorrelation of the transmitted signal as the only side information while allowing the relay, in the best case, to implement precoding as if there was not any self-interference or frequency selectivity in the source-relay channel. Finally, the proposed adaptation algorithm is investigated by determining its stationary points and by performing simulations in a MIMO-OFDM framework.
Keywords: adaptive signal processing; dynacs; full duplex

Cancelling self-interference in full-duplex relays without Angle-of-Arrival information - Emilio Antonio-Rodríguez; R. López-Valcarce (Int. Conf. Acoust., Speech, Signal Process. (ICASSP), 2013)
With full-duplex relays, simultaneous reception and transmission in the same frequency produce self-interference distortion and relay oscillation, hampering reception at the receiver end unless properly mitigated. Previous adaptive methods for self-interference cancellation using multiple receive antennas require knowledge of the direction of arrival of the source signal. We present a novel architecture and adaptive scheme for Amplify-and-Forward relays allowing cancellation without such knowledge. The temporal filter is updated under the property restoral paradigm in order to match the power spectrum of the retransmitted signal to that of the source signal.
Keywords: adaptive signal processing; dynacs; full duplex

An Adaptive Feedback Canceller for Full-Duplex Relays Based on Spectrum Shaping - R. López-Valcarce; Emilio Antonio-Rodríguez; C. Mosquera; Fernando Pérez-González (IEEE J. Selected Areas in Communications, 2012)
Although full-duplex relaying schemes are appealing in order to improve spectral efficiency, simultaneous reception and transmission in the same frequency results in selfinterference, distorting the retransmitted signal and making the relay prone to oscillation. Current feedback cancellation techniques by means of adaptive filters are hampered by the fact that the useful and interference signals are highly correlated. We present a new adaptive algorithm which effectively and blindly restores the spectral shape of the desired signal. In contrast with previous schemes, the novel adaptive feedback canceller has low complexity, does not introduce additional delay in the relay station, and partly compensates for multipath propagation.
Keywords: adaptive signal processing; dynacs; full duplex

Adaptive self-interference suppression for full-duplex relays with multiple receive antennas - Emilio Antonio-Rodríguez; R. López-Valcarce (IEEE 13th Int. Workshop on Signal Processing Advances in Wireless Communications (SPAWC 2012), 2012)
In full-duplex relays, simultaneous reception and transmission in the same frequency results in self-interference which distorts the retransmitted signal and makes the relay prone to oscillation. We present an adaptive feedback canceller for multiple-input single-output (MISO) relays, efficiently combining spatial and temporal processing. The receive array is adaptively steered towards the minimum variance distortionless response (MVDR), whereas the temporal filter update is based on a novel low-complexity spectrum shaping scheme which avoids introducing additional delay in the relay station.
Keywords: adaptive signal processing; dynacs; full duplex